WOMEN, LAW AND POLICY: CHILD MARRIAGE PRACTICES IN INDONESIA - Sonny Dewi Judiasih; Susilowati Suparto; Anita Afriana; Deviana Yuanitasari (NOTARIIL Jurnal Kenotariatan, 2018)
Child marriages are common throughout Indonesia. This is due to a strong influence of Indonesian customs and religion that strongly influence the lives of its people. It is worth pointing that marriage age arrangements in Indonesian Marriage Law reinforces that legal age for men is 19 years and 16 years for women. The 2012 statistics show that Indonesia is the 37th highest in the world in child marriage, while at the Southeast Asian level, this country ranks second after Cambodia. The ranking went up dramatically since in 2016, based on UNICEF, Indonesia ranked the 7th in child marriage worldwide. This means that the practice of child marriage in Indonesia happens, especially to women at the age of 18 years, and there is no discrimination related to the age of marriage. Against this matter, there has been a file for judicial review that demands marriage age for men and women to be pegged at the age of 18 years. However, the Judge of the Constitutional Court, through Decision Number 30-74/PUU-XII/2014, states that age of marriage remains valid for the 19-year-old for man and 16-year-old for women. The struggle does not stop there because at this time, there a national movement of STOP CHILD MARRIAGE formed by civil organisations in cooperation with the Commission of Child Protection and Ministry of Woman Empowerment and Child Protection. This movement sees that the practice of child marriage is a national emergency problem that must be addressed seriously. Further, this movement demands immediate enactment of government regulation in favour of the law which must promptly revise the Marriage Law, especially related to the marriage age.